Rutin ameliorates LPS-induced acute lung injury in mice by inhibiting the cGAS-STING-NLRP3 signaling pathway - Xin Zhou; Zhibin Wang; Yuting Wang; Guofeng Xu; Min Luo; Mengwei Zhang; Yuying Li; Yuying Li (Frontiers in Pharmacology)
IntroductionAcute lung injury (ALI) and its severe form, acute respiratory distress syndrome (ARDS), represent critical respiratory failures with high mortality rates and limited treatment options. While the flavonoid rutin exhibits documented anti-inflammatory and antioxidant properties, its therapeutic mechanisms in ALI/ARDS remain unclear. This study investigated rutin‘s efficacy against lipopolysaccharide (LPS)-induced ALI in mice, with a mechanistic focus on the cGAS-STING pathway and NLRP3 inflammasome activation.MethodsMale C57BL/6 mice were divided into Vehicle control, LPS induction, LPS + rutin co-treatment, and Rutin monotherapy groups. ALI was induced by intratracheal LPS challenge, and rutin was administered via gavage. Proteomics analysis, histological evaluation, immunohistochemistry, TUNEL staining, immunofluorescence, RT-qPCR, western blot, ELISA, and oxidative stress assays were performed to assess the effects of rutin on ARDS.ResultsThe proteomic profiling of lung tissues from LPS-challenged mice identified significant dysregulation of proteins integral to the cGAS-STING cascade and pyroptotic processes. Gene ontology and KEGG pathway analyses underscored the pivotal role of immune and inflammatory responses in ALI, particularly in cytosolic DNA-sensing and NOD-like receptor signaling pathways. Rutin administration significantly alleviated LPS-induced lung injury, reducing oxidative stress, apoptosis, and proinflammatory cytokine levels (IL-6, IL-1β, TNF-α). Mechanistically, rutin demonstrated dual suppression: 1) inhibiting cGAS-STING activation through decreased expression of cGAS, STING, and phosphorylation of TBK1/IRF3 (P<0.05), and 2) attenuating NLRP3-mediated pyroptosis via downregulation of NLRP3-ASC-caspase1-GSDMD signaling (P<0.05). Pharmacological STING inhibition (C-176) validated the cGAS-STING-NLRP3 regulatory hierarchy in ALI pathogenesis.Conclusion:These findings elucidate rutin‘s novel therapeutic mechanism through coordinated suppression of the cGAS-STING-NLRP3 axis, positioning it as a promising candidate for ALI/ARDS intervention.